Microhardness of Cd₁-ₓMnₓTe solid solutions - Dremlyuzhenko, S.G.; Zakharuk, Z.I.; Rybak, E.V.; Yuriychuk, I.M.; Gorbunov, V.V. (Functional Materials, 2006)
The distribution coefficient of Mn (kₛ) in Cd₁-ₓMnₓТе (0.02 ≤ х ≤ 0.55) solid solutions crystals grown by Bridgman technique has been determined using the radioisotope method. Microhardness of Cd₁-ₓMnₓТе solid solutions has been studied by Vickers technique. It is found that the Mn distribution homogeneity along the ingot depends on the synthesis duration. The Mn distribution coefficient for homogenized Cd₁-ₓMnₓТе solid solutions is kₛ = 1. With the increase of manganese content in Cd₁-ₓMnₓТе solid solution up to х = 0.15, the microhardness increases linearly, reaches a maximum, and then some decrease of the microhardness occurs. В выращенных методом Бриджмена кристаллах твердых растворов Cd₁-ₓMnₓТе (0,02 ≤ х ≤ 0,55) проведены определения коэффициента распределения (kₛ) марганца радиоизотопным методом и измерение микротвердости по методу Виккерса. Однородность распределения Mn по слитку зависит от времени синтеза. Коэффициент распределения марганца для гомогенизированных твердых растворов Cd₁-ₓMnₓТе равен kₛ = 1. Микротвердость при увеличении содержания марганца в твердых растворах Cd₁-ₓMnₓТе до х = 0,15 линейно возрастает и достигает максимума, а затем происходит незначительное ее снижение. У вирощених методом Брiджмена кристалах твердих розчинiв Cd₁-ₓMnₓТе (0,02 ≤ х ≤ 0,55) проведено визначення коефiцiєнта розподiлу (kₛ) марганцю радiоiзотопним методом i вимiрювання мiкротвердостi за методом Вiккерса. Однорiднiсть розподiлу Mn вздовж злитку залежить вiд часу синтезу. Коефiцiєнт розподiлу марганцю для гомогенiзованих твердих розчинiв Cd₁-ₓMnₓТе рiвний kₛ = 1. Мiкротвердiсть при збiльшеннi вмiсту марганцю у твердих розчинах Cd₁-ₓMnₓТе до х = 0,15 лiнiйно зростає i досягає максимуму, а потiм вiдбувається незначне її зниження.